Factors influencing the use of learning management system in Saudi Arabian higher education: a theoretical framework - Asiri, Mohammed J. Sherbib; Mahmud, Rosnaini; Abu Bakar, Kamariah; Mohd Ayub, Ahmad Fauzi (Canadian Center of Science and Education, 2012)
The purpose of this paper is to present the theoretical framework underlying a research on factors that influence utilization of the Jusur Learning Management System (Jusur LMS) in Saudi Arabian public universities. Development of the theoretical framework was done based on library research approach. Initially, the existing literature relevant to the subject was reviewed to determine the important variables related to factors influencing the use of LMS in higher education. The paper provides insights of the external and internal variables or factors that influence the use of Jusur LMS for teaching and learning purposes. The internal variables consist of the attitude of Saudi Arabian faculty members towards using LMS, their beliefs towards e-learning, and their competence level in using LMS. The external variables consist of barriers faced by the faculty members and demographic factors. This study was limited to the use of Jusur LMS, one of the e-learning management tools used in Saudi Arabian universities, and surveyed faculty members of Saudi Arabian public universities. This theoretical framework can be adapted to suit the requirements of other similar studies related to planning and implementation of various technology programs in higher education.